Design Tools A reflection towards the definition of a taxonomy - Bruno, Carmen (Design International, 2022)
This book aims at encompassing the panorama of design tools being developed, tested and adopted by researchers and professors at the Department of Design of Politecnico di Milano. The tools are organized in a taxonomy that reflects the path of choice of a possible user in need for the right tool for a task to be performed. The taxonomy is based on a formalization of the design process proposed by the authors, which characterizes the Design System at Politecnico di Milano. The book essentially offers two main contributions: an original taxonomy that guides towards the organization of design tools and their usage with different actors; a representative collection of design tools developed within the Department of Design of Politecnico di Milano with specific instructions on how to use them. Design Tools is addressed both to practitioners and academics in the field of design that are interested in getting to know more about the discourse around design tools in general and in particular how this discourse takes a shape within Politecnico di Milano and resolves in usable and shareable tools.